Transformation Analysis of Carbon and Nitrogen Compounds in Wastewater Treated in a Vertical Biofilter - Dariusz Wawrentowicz (Polish Society of Ecological Engineering (PTIE), 2021)
Biofilter technology for wastewater treatment is relatively complex and is gaining more interest. However, it should be emphasised that various aerobic conditions may occur in biological filter beds, which depend primarily on the velocity of wastewater flow through the bed. Therefore, it is often difficult to precisely determine the transformations of carbon and nitrogen compounds that occur during wastewater treatment on these types of filter beds. This study investigated the effectiveness of the filter bed and analysed the extent of the transformation of carbon and nitrogen compounds in the range of filtration velocities from 0.02 to 0.60 m·h-1. The study was conducted under laboratory conditions, and model wastewater was prepared on the basis of sodium acetate, ammonium chloride, potassium nitrate and potassium dihydrogen phosphate. The model wastewater was prepared with parameters corresponding to those of the treated wastewater. The experiment showed that anaerobic and aerobic conditions occurred in the biological filter bed at filtration velocities of up to 0.16 m·h-1. Above this velocity, aerobic conditions prevailed in the biological filter bed.